Relation of hypoxia-inducible factor-2 alpha (HIF-2 alpha) expression in tumor-infiltrative macrophages to tumor angiogenesis and the oxidative thymidine phosphorylase pathway in Human breast cancer. - Leek, R; Talks, K; Pezzella, F; Turley, H; Campo, L; Brown, N; Bicknell, R; Taylor, M; Gatter, K; Harris, A (2002)
Tumor-associated macrophages (TAMs) produce angiogenic factors and in breast cancer are associated with high vascular grade and poor survival. TAMs preferentially migrate to hypoxic areas within tumors and strongly express hypoxia-inducible factor (HIF)-2 alpha. This study examined whether HIF-2 alpha was involved in TAM angiogenic activation by correlating its expression with tumor microvessel density as a marker of angiogenesis, and other tumor variables, in a series of human primary invasive breast carcinomas. A correlation was found between high TAM HIF-2 alpha and high tumor vascularity (P < 0.0001), as well as high tumor grade (P = 0.007). The relation of HIF-2 alpha expression to a recently described oxygen-dependent pathway of angiogenesis was also studied, and an inverse relationship was found between TAM HIF-2 alpha and tumor thymidine phosphorylase expression (P = 0.02). These results suggest that TAM HIF-2 signaling may be a useful target for future antiangiogenic strategies but show that tumors use both oxygen-dependent and oxygen deficiency-regulated pathways for angiogenesis. Thus, combined blockade of pathways and careful assessment of these pathways in trials are necessary.